Mass events as visual practices in the context of today's culture - A. M. Tormakhova, (Ukrainian Cultural Studies, 2021)
The article analyzes mass events in the context of modern culture. They are seen as visual practices that occupy a leading place in today's culture. Mass events and their organization reflect the trends that characterize modern events. For this purpose, various mass events can be divided into: sports, political, advertising and commercial, business, religious and spiritual-educational, cultural and mass. The mass nature causes the emergence of common features that are inherent in these measures. For the most part, they focus on active participation between spectators and participants, communication between them, which can be carried out both directly and through non-verbal communication. The visual components of all mass events are aimed at promoting awareness of the significance of the event, its purpose, conveying its main message to everyone present. Integrative and communicative function is inherent in all mass events. In the XX-XXI century with the organization of events with the participation of designers, marketers and managers, mass events become even more organized and balanced. They are extremely spectacular; they can involve a full range of tools used in shows. The integration of participants is carried out through artistic and aesthetic factors and certain forms of mass events can claim to become new art practices, due to the significant role of artistic components in them. The visual aspects of such events are the result of design work, which aims to create a corporate identity for all types of design products.Mass events are so impressive in today's culture because they not only promote communication and integration of participants, but also because they cover the full range of expressive technical and artistic means. Many mass events are accompanied by bright fireworks – carnivals, national holidays, the Olympic Games – turning everyday life into a holiday. The impact is also enhanced by working with lighting, projection decorations, video installations, which help to create bright effects without involving bulky equipment.
Keywords: mass events, visual practices, culture, visual design, communication, design